Persistence of environmental DNA in marine systems. (December 2018) - Collins, Rupert; Wangensteen, Owen; O'Gorman, Eoin; Mariani, Stefano; Sims, David; Genner, Martin
Abstract As environmental DNA (eDNA) becomes an increasingly valuable resource for marine ecosystem monitoring, understanding variation in its persistence across contrasting environments is critical. Here, we quantify the breakdown of macrobial eDNA over a spatio-temporal axis of locally extreme conditions, varying from ocean-influenced offshore to urban-inshore, and between winter and summer. We report that eDNA degrades 1.6 times faster in the inshore environment than the offshore environment, but contrary to expectation we find no difference over season. Analysis of environmental covariables show a spatial gradient of salinity and a temporal gradient of pH, with salinity—or the biotic correlates thereof—most important. Based on our estimated inshore eDNA half-life and naturally occurring eDNA concentrations, we estimate that eDNA may be detected for around 48 h, offering potential to collect ecological community data of high local fidelity. We conclude by placing these results in the context of previously published eDNA decay rates. Rupert A. Collins et al. show that environmental DNA degrades faster in the inshore urban environment than the ocean-influenced offshore environment. This study suggests that environmental DNA can be reliably detected for two days, providing an optimal time window of high local fidelity.